Penerapan Sistem Pengendalian Intern atas Persediaan Barang pada PT.Mica Jaya Pratama - Pungky Rahmawanti; Endang Masitoh; Anita Wijayanti (Politeknik Ganesha Medan, 2020)
This study aims to find out how the application of internal control over inventory of goods at PT Mica Jaya Pratama Solo. This research is a qualitative research that is by conducting both structured and unstructured interviews to determine the internal control carried out by the company. In this study the variables are the principles of internal control such as adequate separation of duties (organizational structure), determination of adequate responsibilities (system of authority), design and use of documents and adequate records (healthy practices), physical control of assets and records adequate (healthy practice), independently verify performance (HR). The result of this study is that the inventory control system at PT. Mica Jaya Pratama is in accordance with the SOP, but in an adequate separation of duties there is no division between the purchasing division and the finance division.